The airway smooth muscle in asthma - Black, Judith (Henry Stewart Talks, 2011)
Remodelling of the asthmatic airway, Airway smooth muscle (ASM), increased deposition of matrix proteins, Asthma increases ASM, Characteristics of ASM cells in non-asthmatics, Characteristics of ASM in asthmatics, ASM produces extracellular matrix (ECM) proteins, Differences in ECM in asthmatics, Fibulin-1 in asthma, Fibulin as a therapeutic target